Potential of low-temperature geothermal resources in northern California. Report No. TR13 - Hannah, Judith L. (California. Division of Oil and Gas., 1975)
Economically feasible uses for geothermal heat at temperatures too low for conventional electrical power generation at present are delineated. Several geothermal resource areas in northern California that have development potential are described, and applications of the heat found in each area are suggested. Plates are included of the following field study areas: the east side of the Sierra-Cascade Range north of Bishop, and the northern Coast Range from San Francisco Bay to Clear Lake. The counties included in the study area are Mo doc, Lassen, Sierra, Plumas, Placer, Alpine, Mono, Mendocino, Lake, and Sonoma. (LBS)